2010
DOI: 10.1111/j.1600-0463.2009.02570.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin production by Shigella sonnei isolated from faeces of children with acute diarrhoea

Abstract: Shigella is a common agent of diarrhoea, a worldwide major health problem. The bacterium produces bacteriocins; however, the role of these substances as a virulence factor is completely unknown. With the aim to search for colicin production by Shigella sonnei, to evaluate the influence of culture conditions on bacteriocin expression, and to characterize the substance partially, 16 S. sonnei strains isolated from children with diarrhoea were tested for antagonism against members of the intestinal microbiota or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 36 publications
(64 reference statements)
3
30
0
3
Order By: Relevance
“…In addition to the emergence of resistance, the impact of the toxin on the commensal microbiota also deserves equal attention, before therapeutic applications commence. Several studies have shown that colicins leave the structure of the commensal microbiome largely undisturbed (18,19). In our case, we found that the majority of commensal E. coli strains (85%, n ϭ 20) were colicin resistant.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In addition to the emergence of resistance, the impact of the toxin on the commensal microbiota also deserves equal attention, before therapeutic applications commence. Several studies have shown that colicins leave the structure of the commensal microbiome largely undisturbed (18,19). In our case, we found that the majority of commensal E. coli strains (85%, n ϭ 20) were colicin resistant.…”
Section: Discussionsupporting
confidence: 50%
“…Among the colicins produced by Shigella strains, colicin U and colicin Js are expressed by S. boydii and S. sonnei, respectively (15)(16)(17). A few studies have demonstrated that S. sonnei colicins exhibit antagonism against some of the shigellae and DEC, which are sometimes uncontrollable by any antimicrobial therapy (18). Hence, strategies for designing newer antibiotics with different modes of action are now being considered.…”
mentioning
confidence: 99%
“…Oxidative stress could, in general, slightly impact the growth of LAB, since they are defined as aerotolerant microorganisms though different behavior had been detected for bacteriocin production in various atmospheric incubation conditions (7,17,19,27). …”
Section: Discussionmentioning
confidence: 99%
“…Bacteriocins have been reported to be produced by several enteric bacteria including S. sonnei , S. flexneri , and S. boydii . They are usually designated as colicins (Horak 1994; Padilla et al , 2006; Smajs and Weinstock 2001; Smajs et al , 1997; Smarda et al , 1987; Sousa et al , 2010). Colicin genes are found mostly in colicinogenic plasmids of Gram-negative E. coli (Cascales et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There are at least 23 colicin types have been described in detail (Smajs and Weinstock 2001). It has been reported that S. sonnei , S. flexneri , and S. boydii produce colicin (Horak 1994; Padilla et al , 2006; Smajs and Weinstock 2001; Smajs et al , 1997; Smarda et al , 1987; Sousa et al , 2010); however, there are only a few reports on the characterization of bacteriocin from S. sonnei (Smarda et al , 1987; Sousa et al , 2010; Tigyi 2005). The aim of this study was to determine the colicin production by S. sonnei strain isolated from Thai patients with diarrhoea and to characterize its properties.…”
Section: Introductionmentioning
confidence: 99%